Trust of Information Technology Governance in High School Institution (HSI): A Conceptual Framework - Resad Setyadi; Aedah Abd Rahman; Aang Subiyakto; Anwar Fattah (International Journal of Science, Technology & Management, 2021)
This study aims to build a conceptual framework for previous research. This research is related to High School Institutions (HSI) readiness and usability that provides Information Technology Governance Trust (ITGT). The findings based on the literature review provide the initial construction and subsequently become a model conceptual framework. The comparison results with previous research indicate an influence between readiness and usability to user trust when implementing Information Technology Governance (ITG.) in an institution. The impact was identified through past literature, namely assessing the relationship between the Readiness Domain and the Usability Domain towards ITG. By testing high school institutional users (HSI), a trust will be through testing to develop a framework model research.